Prática pedagógica discursiva de professores indígenas da educação de jovens e adultos e o fortalecimento da cultura Potiguara-PB - Silva, Maria Alda Tranquelino da (2022)
Indigenous School Education and in it the EJA modality are understood as a still recent educational paradigm in the Brazilian scenario, permeated by advances, limits and throwback. In this sense, this research is focused on the discursive elements identified in the context of the pedagogical practices of indigenous teachers that contribute to the strengthening of the Potiguara culture, which is located on the north coast of Paraíba. Specifically, this proposed work: 1) Analyze the legal provisions that deal with EJA and Indigenous School Education, intersecting them with the two modalities in question; 2) Understand the concept of pedagogical practice in EJA, which is present in the theoretical references and discussed as a modality on screen, as well as the elements of culture in the direction of strengthening it; 3) Discuss the concept of indigenous cultures and Potiguara indigenous culture, which are presented from the speeches presented in the legal provisions and indigenous literature in the modality of EJA School Education; 4) Systematize the pedagogical elements found in the discursive pedagogical practices of teachers working in EJA, as a strengthening of culture. Therefore, this research is anchored in authors such as: Barcellos (2014), Nascimento (2012), Munduruku (2009), Kayapó (2019), Silva (2017), Silva e Costa (2018), Silva (2020), Soares ( 2006) and Pimenta (2012), as well as current legislation. This is a qualitative approach research, whose analysis and generation use the survey, semi-structured interviews, that occurred in 2021, with indigenous teachers who worked in EJA, in the cities of Rio Tinto, Marcação and Baia Traição, in the state of Paraíba. Regarding the data analysis, using the Discourse Critique pre-conized by Fairclough (2016), an important instrument to study the pedagogical practice of the teachers in question, observing as an analysis for the strengthening of the Potiguara indigenous culture in the EJA modality. As a conclusion of the findings, research highlights the thesis that contextualized education, indigenous protagonism, criticism, participation and materialization, organization and dialogue are presented in discursive pedagogical actions, of this word by teachers indigenous elements in the EJA modality, in schools in Potiguara communities, as it contributes to the strengthening of culture; constituting the resistance action of this population on the north coast of Paraíba, facing the challenges of the posts when facing the education models and trying to homogenize, the culture and integrate the indigenous population and, specifically, the young and the adult. In this way, it is pointed out the need to promote indigenous pedagogical practices, in a contextualized way with the EJA modality, as well as the need for new resources on the modality on screen, and the educational policies that discuss, problematize, reflect and point out ways for an Indigenous School Education, in the form of EJA, of valuing and respecting cultures.